10.1016/0967-0653(93)95658-s (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Establishment of the gut microbiome during the first years of life is critically important for long-term health and development. In preterm infants, microbial colonization is disrupted due to their developmental immaturity and the myriad of pre- and postnatal exposures. Unfortunately, this places them at an elevated risk for adverse health outcomes into childhood (eg, asthma and impaired neurodevelopment). Understanding the developmental trajectory of the microbiome in preterm infants, the factors predicting these microbial patterns, and the links to childhood health can offer opportunities to develop interventions and optimize health. OBJECTIVE: BLOOM (Begin a Life of Health With Observation and Optimization of the Microbiome) is a prospective, observational cohort study that aims to examine how early-life microbiomes shape the health and development of preterm infants into childhood (eg, asthma and neurodevelopment). METHODS: Infants (<37 weeks gestation) and their families are recruited from 4 neonatal intensive care units in Calgary, Alberta, Canada. Maternal stool and weekly infant stool, urine, and human milk samples are collected during the first 2 months postnatally; participants are then followed up at 3 months, 1 year, and 3 years corrected age for continued data (eg, nutrition, medications, medical history, and home environment) and sample collection (stool, urine, nasal swabs, hair, and blood). Additional clinical testing (eg, allergen skin prick test) and questionnaires (eg, Ages & Stages Questionnaires, Third Edition) are administered to assess health outcomes and developmental milestones. RESULTS: Study recruitment and data/sample collection for BLOOM commenced in 2019; as of May 2026, we have enrolled 245 participants, and recruitment is ongoing. An initial characterization of early-life microbiome profiles for the first 105 infants enrolled in BLOOM was published online in December 2025. CONCLUSIONS: BLOOM is a large, comprehensive prospective cohort study and biobank aimed at measuring the microbiome development of preterm-born children. This cohort will address significant research priorities through characterizing the patterns of microbiome development in preterm infants over the first 3 years postnatally and correlating these with health outcomes (eg, immune development, asthma and allergy risks, and neurodevelopment). It is anticipated that the results can be leveraged to identify factors and altered microbiome patterns underlying disease risk, design intervention strategies (eg, microbial therapeutics) for later clinical testing, and generate novel hypotheses of possible underlying mechanisms linking microbiome development to health.